Interaksi antara Pemerintah Provinsi Daerah Khusus Jakarta dan Kearifan Lokal: Menciptakan Harmoni dalam Pembangunan Kota - Citrawali, Andi; Tjenreng, Muhammad Baharuddin Zubakhrum (Jurnal PKM Manajemen Bisnis, 2025)
Jakarta, currently undergoing a transition from its status as a Special Capital Region to the Special Region of Jakarta following the enactment of the DKJ Bill by the Indonesian House of Representatives on Thursday, March 28, 2024, will no longer serve as the nation's capital once the new National Capital City (IKN) is officially inaugurated. Jakarta, with its dynamic urban life, must continue to progress and develop to better serve and support its residents, ensuring a prosperous, safe, and peaceful life. The city’s development should focus on human resource development based on local wisdom, considering its dense population, social complexity, and limited natural resources compared to other regions. Harmonious urban development can be achieved through positive interaction between the government and local wisdom, along with policies oriented toward social, cultural, and environmental sustainability. This approach aims to make Jakarta a livable and globally competitive city while preserving its unique cultural identity.